Public Sector Capacity to Prevent and Control of Noncommunicable Diseases in Twelve Low- and Middle-Income Countries Based on WHO-PEN Standards: A Systematic Review - Ahmed Hassan Albelbeisi; Ali Albelbeisi; Abdel Hamid El Bilbeisi; Mahmoud Taleb; Amirhossein Takian; Ali Akbari-Sari (SAGE Publishing, 2021)
This review was conducted to assess the capacity of the public sector to prevent and control noncommunicable diseases (NCDs) in low-and middle-income countries (LMIC) based on WHO-PEN standards. A PRISMA systematic search appraisal of PubMed, Scopus, and Embase was conducted during May-2020 for original articles conducted in LMIC and reported the capacity of the public sector to prevent and control NCDs. The country readiness score was calculated as the mean score of items for each domain. The indices were compared to an agreed cutoff at 80% the WHO optimal target of availability of affordable essential medicines and basic technologies required to treat NCDs. The literature search yielded 5 original studies, conducted in twelve countries, and surveyed 304 public health facilities. All countries failed to reach the WHO optimal target of availability of affordable essential medicines and basic technologies. The readiness index score according to WHO-PEN standards among countries in terms of essential medicines, diagnostic investigations, and basic equipment were range from 13.5% to 51%, 0.0% to 59.4%, and 29.2% to 51.2% respectively. This review revealed critical gaps in the twelve LMIC public sector capacity to prevent and control of NCDs in terms of essential medicines, basic equipment, and diagnostic investigations.